Difference Sequence Spaces and Matrix Transformations - Joshi, Geeta Bhakta; Mishra, Shailendra Kumar; Rajpant, Shankar (Journal of the Institute of Engineering, 2009)
In this paper, we extend the work of Gaur, A.K. and Mursaleen [6] and also extend the work of Mursaleen, Gaur, A.K. and Saifi, A.H.[16]. We characterize the matrices that map S (p,D) r , ¥ (p) Dl , c (p) 0 D , Dc(p)and ( p) r D ¥ l into W(t ). Key words: matrix transformations Journal of the Institute of Engineering, Vol. 7, No. 1, 2009, July pp. 24-30 doi: 10.3126/jie.v7i1.2059